Edukasi Pemanfaatan Cagar Budaya Kabupaten Pengandaran Melalui Program Sportourism - Ruman; Dian Imam Saefulah; Diyah Kusuma Ningrum (Pusat Riset dan Inovasi Nasional, 2022)
Thematic Real Work Lectures (KKN) or also commonly called KKN-T are KKN whose activity program orientation is focused on certain fields in accordance with social problems and the direction of development policies implemented by the government in certain areas (Regency/City). The implementation of Thematic KKN is intended to foster empathy and concern among the academic community of STKIP Darussalam Cilacap towards, (1) various real problems faced by society and (2) sustainable development which is needed to make the nation's life intelligent and realize social welfare. The implementation of the Sporturism activity program carried out in Panggung Cave, Pengandaran Regency, was carried out on Tuesday, March 15 2022, from which the authors concluded that the people in Pengandaran Regency still do not realize the potential that if Panggung Cave is utilized optimally, it will obtain better benefits. This is proven by the way the authors conducted observations and short interviews with local communities and visitors.